Mobilidade ascendente, identidade e estilos de vida do negro (a) no interior paulista: o caso de São Carlos e Araraquara - Martins, Thais Joi (2009)
This work has the focus to bring reflection about identity and trajectory of some black professionals and businessman from west of the State of Sao Paulo. We search to know how these black people walk their path and lifestyle and meaning and remaining their identity when reach important posts and positions at the work market, that is, when reach a raising social and economic mobility. In this way, first counting on a bibliographic review about the thematics cited above and subsequently with an analytic descriptive moment that will count on exposition and analysis of the data obtained in interviews made with middle class black people from local authority of Sao Carlos and Araraquara. It has also the intention to do a qualitative analysis so we can get more precisely results for reflection in a conclusive way about the construction of the black people s identity and insertion in the Brazilian work market.